SCIENTIFIC AND APPLIED GEOGRAPHICAL IMPORTANCE OF THE FORTIFICATION LANDSCAPES RESEARCH - Денисик, Г.; Антонюк, О. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2019)
Importance of fortification landscapes is insufficiently appreciated in Ukraine. There is no clearly defined structure, classification, zoning of fortification landscapes. Unlike other classes of anthropogenic landscapes is not defined their role and place in the modern landscape structure and certain regions of Ukraine. Underestimated importance of fortification complex landscape as a historical and cultural and natural heritage. Recently, the intensive processes of offensive forced towards natural, historical and cultural monuments has been activated, manifesting uncontrolled change in the status and ownership of the land fund, monuments and protected areas of all kinds and types, and others. If these trends continue to be stored - it will be a real challenge to science and social needs. The risk is that mostly archaeological, historical, cultural and natural attractions often occupy a small area and easy to destroy. To restore them is impossible. Fortification landscapes research as historical and natural heritage shows that they cannot be studied separately, because they are for centuries and even millennia have adapted to the surrounding landscape, have become parts of other landscapes. Most areas of existing and planned protected areas and sites of Ukraine and, especially Podylla, have a complex multi-stage anthropogenic origin. Anthropogenic landscapes, including fortification landscapes by modern approaches are self-sufficient and significant monuments, formed as a result of a complex interaction of natural and sociohistorical factors. Problems integrated approach to fortification landscape conservation related to insufficient study of natural and cultural heritage, including fortification landscapes as a complex of monuments; inconsistency and isolation of archaeological, historical, geographical, landscape, environmental and other studies not only the individual, according to science, objects, but sometimes one and the same object in different sciences; imperfect legal framework. However, this leads to the fact that at the beginning of XXI century mounds, mounts and other fortification landscape complexes have been considered by scientists only as historical or military objectives, and only occasionally as a kind of man-made landscape complexes. Current approaches to the conservation of fortification landscapes should be based on two main principles: indivisibility of natural and cultural heritage and their spatial alignment. Keywords: fortification landscapes, historical and cultural heritage, natural heritage, the inseparability of natural and cultural heritage, spatial alignment, conservation, preservation.